Phase transitions and optical properties of the trigonal perovskite (CH3NH3)2TeCl6 - Liu, Y; Cockcroft, JK; Chen, Z; Hayward, MA; Henry, PF; Perry, RS; Palgrave, RG (Royal Society of Chemistry, 2022)
Vacancy-ordered double perovskites A2BX6 are attracting attention due to the isolated octahedra making them an ideal playground for studying perovskite structure-property relationships. MA2TeCl6 single crystals have been successfully grown from solution. X-ray structure experiments as a function of temperature have demonstrated two structural phase transitions: from cubic Fm3̄m (high temperature, phase I) to trigonal P3̄m1 (intermediate temperature, phase II) at 460 K and then to trigonal P3̄1c (low temperature, phase III) at 200 K. Intriguingly, we observe a negative thermal expansion for the c-axis in phase II believed to caused by dynamic tilting of the C–N bond in the MA+ ion. We have modified and extended the calculation of the Brown radii ratio in the perovskites to include hybrid A2BX6 compounds by selecting the shortest A–X distance for the ratio equation. We find that for ratios between 0.89 and 1.17, typically the Fm3̄m cubic structure is observed, while for ratios above 1.17, mostly distorted structures are found.